Professional Ethics Of Primary School Teachers In Educating Students’ Character And Morals - Amiruddin, Amiruddin; Rozai Iskandar; Buyung Satrio Dasopang; Ajeng Kiana Putri; Fahri Dharma (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2024)
Character and moral education are crucial aspects in shaping the personal development of elementary school students. Teachers, as primary agents in the educational process, bear significant ethical responsibilities in guiding and fostering the moral growth of their students. This literature review adopts a descriptive approach to explore the pivotal role of elementary school teachers in educating students' character and morals, as well as the ethical challenges they encounter in this endeavor. The study reviews existing literature to identify effective strategies for integrating character education into the elementary school curriculum. The findings of this review are expected to contribute to strengthening ethical professionalism among teachers and enhancing the quality of moral education at the elementary level.